Digitalna transformacija v logistiki in managementu oskrbovalnih verig (University of Maribor Press, 2025)
Digital Transformation in Logistics and Supply Chain Management. The higher education textbook *"Digital Transformation in Logistics and Supply Chain Management"* is a comprehensive guide aimed at supporting digitization and digital approaches in logistics. It focuses on process digitalization, the use of tools far digital data processing and simulations, autonomous vehicles, machine learning in logistics processes, and cybersecurity. This interdisciplinary approach combines knowledge from various fields-computer science, information technology, mechatronics, machine learning, simulation methods, and business decision-making, providing a thorough understanding of digital logistics challenges and the application of practical knowledge to areas beyond logistics and supply chains. Readers are equipped with practical knowledge and skills to improve the efficiency and transparency of individual processes. The textbook covers topics such as: 1) Process Digitization - Planning; 2) Process Digitization - Execution; 3) Business lnformation Systems; 4) Simulations and Digital Twins; 5) Autonomous Vehicles in Logistics; and 6) lnformation Security. The entire content is focused on strengthening digital competencies essential for effectively managing modem logistics companies and building resilient supply chains.